Acculturation Orientation of Post-Millennial Generation in Java: Harmonizing Local Culture and Global Modernity - Wicaksana, Bintang Sasmita; Yuniardi, M. Salis; Syakarofath, Nandy Agustin (Universitas Negeri Medan, 2024)
The collision between modernity and local cultural values often emerges. This research aims to empirically investigate the distinction of acculturation orientation between modernity caused by global culture and traditional Javanese values among the post-millennial Javanese generation. This is descriptive-quantitative research involving the Javanese post-millennial generation with the year of birth between 1997 and 2009 sampled through purposive sampling. The research instrument is the Vancouver Index of Acculturation that has been contextualized by the research. The results show that there is a variety of acculturation orientation types among the Javanese post-millennial generation: 88,4% is in the integration orientation group, 6,4% is in the separation orientation group, 3,5% is in the assimilation orientation group, and 1,7% is in the marginalization orientation group. Moreover, there are research findings differentiated based on the respondents’ sex and place of origin.